Assessing Multidimensional Productive Zakah Utilization Using a Modified Zakah Utilization Index: Evidence from the BAZNAS Microfinance Desa Program in Mojokerto, Indonesia - M. Maulana Asegaf; Lian Fuad; Siti Marpuah (Al Ahkam, 2026)
Productive zakah serves as a critical instrument of Islamic social finance for advancing sustainable, multidimensional empowerment of mustahik. Given that empowerment encompasses social, cultural, and environmental dimensions beyond economic improvement, comprehensive, multidimensional evaluation frameworks are essential for assessing the effectiveness and sustainability of productive zakah programs. However, empirical studies utilizing integrated multidimensional empowerment indicators remain scarce. This study evaluated the effectiveness of the utilization of productive zakah in the BAZNAS Microfinance Desa (BMD) Program in Mojokerto City, using the Modified Zakah Utilization Index (Modified IPZ), a multidimensional framework for measuring empowerment across social, cultural, economic, and environmental dimensions. Employing a descriptive quantitative methodology, primary data were collected via questionnaires from 31 mustahik and semi-structured interviews with staff of BAZNAS Mojokerto City. Data were analyzed using the Modified IPZ framework and descriptive statistical analysis. Results yielded an overall Modified IPZ score of 0.50, indicating empowerment at the strengthening stage without yet achieving sustainable economic self-reliance. The social dimension recorded the highest performance (0.70), while cultural (0.39), economic (0.45), and environmental (0.48) dimensions remained below target levels. These findings indicate that entrepreneurial capacity, economic resilience, and environmental literacy require substantive strengthening to achieve holistic and sustainable empowerment. The study demonstrates that the provision of productive capital alone is insufficient and must be complemented by integrated support mechanisms, including continuous business mentoring, systematic entrepreneurship development, sustainable market linkages, targeted financial literacy programs, and environmental sustainability awareness.